Efficient Total Synthesis of (±)-Isoguaiacin and (±)-Isogalbulin - Pilkington, Lisa I.; Song, Soo Min; Fedrizzi, Bruno; Barker, David (Synlett, 2017)
1-Arylnaphthalene lignans such as (–)-isoguaiacin and (–)-isogalbulin have been reported to exhibit notable biological properties. While (–)-isoguaiacin has not been previously synthesized, syntheses of (–)-isogalbulin are generally long and produce a mixture of stereoisomers. We herein present the efficient total synthesis of (±)-isoguaiacin and (±)-isogalbulin in seven and eight steps with an overall yield of 46% and 36%, respectively. The reported approach harnesses a hydrogenolysis reaction in acidic conditions, to convert a furan into an arylnaphthalen structure.
Keywords: lignan; 1-arylnaphthalene; synthesis; Paal–Knorr; cyclization